2017
DOI: 10.1039/c7ra05674e
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich-structured rGO/PVDF/PU multilayer coatings for anti-corrosion application

Abstract: We successfully construct rGO/PVDF/PU sandwich-structured composite coatings. The composite film demonstrates excellent anti-corrosion effects for metal protection due to its strong mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Coatings generally provide mechanical [396], chemical [397] and weathering [398,399] protection that increases resistance to wear, and this can be achieved through polymeric and smart coatings. Polymeric coatings (e.g., PDMS [400,401], PMMA [179,402] and PVDF [403][404][405]) can form organic thin films onto a substrate to significantly modify surface reactivity towards various elements including corrosion, adhesion, and wear [406]. Likewise, inorganic coatings (e.g., graphene [407], Ag [408] and Au [409]) can modify surface properties providing corrosion and damage protection.…”
Section: Self-protectionmentioning
confidence: 99%
“…Coatings generally provide mechanical [396], chemical [397] and weathering [398,399] protection that increases resistance to wear, and this can be achieved through polymeric and smart coatings. Polymeric coatings (e.g., PDMS [400,401], PMMA [179,402] and PVDF [403][404][405]) can form organic thin films onto a substrate to significantly modify surface reactivity towards various elements including corrosion, adhesion, and wear [406]. Likewise, inorganic coatings (e.g., graphene [407], Ag [408] and Au [409]) can modify surface properties providing corrosion and damage protection.…”
Section: Self-protectionmentioning
confidence: 99%
“…These results indicate that the AlGO/PI coating possesses better anticorrosion properties than the GO/PI coating. The superior anticorrosion performance can be attributed to the insulating layer of alumina on GO, which isolates the electron transfer pathways between the GO and CRS metals, thus inhibiting the corrosionpromotion activity of the graphene [51,52].…”
Section: Barrier Properties Of Pi Nanocomposite Filmsmentioning
confidence: 99%
“…In addition, several authors reported the corrosion inhibition barrier layers in the 3.5% NaCl environment, prepared from graphene oxides functionalized with pyridine as well as composites of graphene oxide with polystyrene, metronidazole, polyvinylene and lignin. [11][12][13][14][15][16][17][18] Moreover, the rare earth elements have been reported as green corrosion inhibitors because of their biocompatibility and the ability to transfer electrons to the vacant metal d orbitals. It is also known that the lanthanide series elements can improve the long-term corrosion inhibition efficiency because they have multiple oxidation states.…”
Section: Introductionmentioning
confidence: 99%